Improvement of solubility and analysis thermodynamic properties of β tegafur in pure and mixed organic solvents. (July 2020) - Yang, Zehui; Shao, Danfeng; Zhou, Guoquan
Graphical abstract: Highlights: Research on the dissolution behavior of β form of tegafur in different solvents. The (KAT-LSER) model was applied to analyze solute-solvent interactions. The result of solubility data was discussed and correlated by different thermodynamic models. Some of apparent thermodynamic properties for the dissolution process were also evaluated. Abstract: The purpose is to study the dissolution behaviour for β form of racemic tegafur with therapeutic purpose in different solvent, and select suitable co-solvent to improve dissolving capacity. Before and after experiment, tegafur existed in the form of β in all studied solvents. The solubility values were obtained by using the isothermal equilibrium method and correlated with the modified Apelblat equation and Jouyban-Acree model. In pure solvent, the largest data at 313.15 K was found in acetone (3.875 × 10 −2 in mole fraction), and followed by ethyl acetate (1.748 × 10 −2 ), methanol (1.255 × 10 −2 ), ethanol (0.767 × 10 −2 ), n -propanol (0.618 × 10 −2 ) and iso propanol (0.545 × 10 −2 ). In systems of (acetone + ethanol), the solubility increased monotonically with the increase of temperature and acetone mass fraction. While in mixture of (ethyl acetate + ethanol), it increased at first and then decreased with the increasing mass fraction of ethyl acetate. Moreover, the effect of the solute-solvent intermolecular interactions on the solubility in pure and mixed solvents was discussed. In the following, the analysis of apparent thermodynamic analysis indicates that the dissolution is an endothermic, spontaneous and entropy driven process. More importantly, the effect of co-solvent on the dissolution process of β tegafur is important to its recrystallization and purification.